FINANCIAL TECHNOLOGY ADOPTION, FINANCIAL LITERACY, AND WORKING CAPITAL AS DETERMINANTS OF MSMEs’ FINANCIAL PERFORMANCE: EVIDENCE FROM SUMENEP REGENCY - Sufiyanto Sufiyanto; Moh. Baqir Ainun (Sampoerna University, 2026)
The rapid development of financial technology (FinTech) has increased the importance of financial performance for micro, small, and medium enterprises (MSMEs), particularly in developing regions. This study examines the effect of financial technology adoption, financial literacy, and working capital on the financial performance of MSMEs in Sumenep Regency. Using a quantitative approach, data were collected through questionnaires from 74 MSME owners and analyzed using multiple linear regression. The results indicate that financial technology adoption and working capital have a positive and significant effect on financial performance, while financial literacy shows no significant influence. However, the three variables jointly have a significant impact on MSME financial performance. These findings highlight the importance of digital financial adoption and effective working capital management, while emphasizing the need for practical support to enhance the effectiveness of financial literacy initiatives.